A Study on the Cross-Cultural Communication Attributes Of Translation (International Journal of Language, Literacy and Translation, 2025)
Human culture is rich and colorful, as well as its communication activities and contents. Especially after entering the human society into the information age, the field of human communication activities has been further expanded, revealing that the content of communication has different nature and characteristics. Communication theory has been widely used in social, cultural, economic, scientific and technological activities. It shows the application and promotion of modern communication research in various fields of social life. Cross-cultural communication is a phenomenon in which various cultural resources and cultural information in human societies of different cultures change, interact, and are shared in time and space. Based on the relationship between culture and communication, cross-cultural communication research mainly analyses the changes of heterogeneous culture in the process of communication and the impact of cultural changes on communication, discussing the impact and influence mode of communication on human cultural consciousness, cultural behaviour and cultural customs.